2019
DOI: 10.3390/ma12040617
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Nanoparticles—Current and Prospective Medical Applications

Abstract: The recent, fast development of nanotechnology is reflected in the medical sciences. Superparamagnetic Iron Oxide Nanoparticles (SPIONs) are an excellent example. Thanks to their superparamagnetic properties, SPIONs have found application in Magnetic Resonance Imaging (MRI) and magnetic hyperthermia. Unlike bulk iron, SPIONs do not have remnant magnetization in the absence of the external magnetic field; therefore, a precise remote control over their action is possible. This makes them also useful as a compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
312
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(313 citation statements)
references
References 118 publications
0
312
0
1
Order By: Relevance
“…Physical Pulsed laser ablation [6,[39][40][41]] Pyrolysis [6] Chemical Co-precipitation [3,6,16,[36][37][38][40][41][42][43]] Microemulsion [6,37,44] Hydrothermal and solvothermal syntheses [1,3,6,38] Thermal decomposition [6,38] Sol-gel synthesis [3,16,17,21,32,37,38,[43][44][45][46]] Sonochemical [43,47] Microwave-assisted synthesis [6,48] Biological Biosynthesis [6,49] The synthesis of these nanoparticles into formulations should also be considered. These methodologies aim for the production of IOMNPs with improved characteristics of stability, biocompatibility, high dispersibility, suitable shape, and controlled size [1,3,6,17].…”
Section: Methods Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical Pulsed laser ablation [6,[39][40][41]] Pyrolysis [6] Chemical Co-precipitation [3,6,16,[36][37][38][40][41][42][43]] Microemulsion [6,37,44] Hydrothermal and solvothermal syntheses [1,3,6,38] Thermal decomposition [6,38] Sol-gel synthesis [3,16,17,21,32,37,38,[43][44][45][46]] Sonochemical [43,47] Microwave-assisted synthesis [6,48] Biological Biosynthesis [6,49] The synthesis of these nanoparticles into formulations should also be considered. These methodologies aim for the production of IOMNPs with improved characteristics of stability, biocompatibility, high dispersibility, suitable shape, and controlled size [1,3,6,17].…”
Section: Methods Referencesmentioning
confidence: 99%
“…Moreover, they were investigated as carriers for active agents for drug targeting [6]. In the last few decades, several studies showed the development of preparations containing IOMNP to be used for in vitro separation, tissue repair, cellular therapy, magnetic separation, magnetic resonance imaging, as spoilers for magnetic resonance spectroscopy, in drug delivery, hyperthermia, sensors for metabolites, and other biomolecules [6,11,12,16,18,30,[32][33][34][35].…”
Section: Iron Oxides and Nanoparticlesmentioning
confidence: 99%
“…Besides, colloidal IONPs such as ultrasmall superparamagnetic iron oxide (USPIO) and superparamagnetic iron oxide (SPIO) have already been used as MRI CAs in targeting drug delivery (Busquets et al, 2014;Dulińska-Litewka et al, 2019). Superparamagnetic iron oxide nanoparticles (SPIONs), with the iron oxide core and magnetic coating, have fundamental features such as high saturation magnetic moment, relatively stable chemical properties, and minimized potential toxicity (Busquets et al, 2014;Dulińska-Litewka et al, 2019). They can improve the MRI sensitivity by serving as in vivo or in vitro CAs and thus have potential biomedical applications for MRI CAs (Busquets et al, 2014;Dulińska-Litewka et al, 2019).…”
Section: Commonly Used Mri Casmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles (SPIONs), with the iron oxide core and magnetic coating, have fundamental features such as high saturation magnetic moment, relatively stable chemical properties, and minimized potential toxicity (Busquets et al, 2014;Dulińska-Litewka et al, 2019). They can improve the MRI sensitivity by serving as in vivo or in vitro CAs and thus have potential biomedical applications for MRI CAs (Busquets et al, 2014;Dulińska-Litewka et al, 2019). The commonly used MRI CAs are briefly summarized in Table 1.…”
Section: Commonly Used Mri Casmentioning
confidence: 99%
See 1 more Smart Citation